Prevalence of Sexual Abuse against Male Children Enrolled in Rehabilitation Centers of the Kathmandu Valley - Khanal, Archana; Shakya, Sirjana (Patan Prospective Journal, 2022)
This study is based on the prevalence of sexual abuse against male children and was conducted in two rehabilitation centers located in the Kathmandu Valley. Thirty male respondents from two rehabilitation centers located at Boudha and Lubhu were taken for research sampling. The study is descriptive and exploratory in nature, in which both primary and secondary data have been used. Face-to-face interviews with respondents, key informants’ interviews, and a questionnaire were used to collect the primary data. The qualitative data analysis software, NVivo, was used to code and classify the transcription into different themes. Analytical and descriptive methods were used to analyze and interpret the data. Due to a lack of awareness, victim support, and robust police investigations, street children are victims of all types of child abuse. Boys on the street are given drugs, which eventually cause addiction and make it simple for abusers to turn kids into puppets. Abusers prey on their frailty by offering them cash, gifts, and drugs.